2000
DOI: 10.1073/pnas.97.1.472
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of PDE7B, a cAMP-specific phosphodiesterase

Abstract: A member of the phosphodiesterase (PDE)7 family with high affinity and specificity for cAMP has been identified. Based on sequence homologies, we designate this PDE as PDE7B. The fulllength cDNA of PDE7B is 2399 bp, and its ORF sequence predicts a protein of 446 amino acids with a molecular mass of 50.1 kDa. Comparison of the predicted protein sequences of PDE7A and PDE7B reveals an identity of 70% in the catalytic domain. Northern blotting indicates that the mRNA of PDE7B is 5.6 kb. It is most highly expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(93 citation statements)
references
References 14 publications
2
90
1
Order By: Relevance
“…These data indicate that these PDEs do not contribute significant cAMP hydrolysis in DLBCL. In addition, in agreement with earlier work, 18,19 but contrary to a recent report in chronic lymphoid leukemia (CLL), 20 we found that PDE7B is not expressed in lymphoid cells (DLBCL) and that the PDE7-specific inhibitor BRL-50481 is largely ineffective in DLBCL cell lines (data not shown). These data suggested that the observed cAMP-mediated inhibition of SYK is directly controlled by PDE4B expression/activity.…”
Section: Camp Inhibits Syk Activity In Normal B Cellscontrasting
confidence: 56%
“…These data indicate that these PDEs do not contribute significant cAMP hydrolysis in DLBCL. In addition, in agreement with earlier work, 18,19 but contrary to a recent report in chronic lymphoid leukemia (CLL), 20 we found that PDE7B is not expressed in lymphoid cells (DLBCL) and that the PDE7-specific inhibitor BRL-50481 is largely ineffective in DLBCL cell lines (data not shown). These data suggested that the observed cAMP-mediated inhibition of SYK is directly controlled by PDE4B expression/activity.…”
Section: Camp Inhibits Syk Activity In Normal B Cellscontrasting
confidence: 56%
“…However, the description of different cAMP pools [30] for PDE4 and PDE7, and the fact that PDE7 acts on low concentrations of cAMP [14] may explain the differences observed in allergic models between the two isoenzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Within the PDE7 family, two isoforms have been cloned in mice, rats and humans, namely PDE7A [12] and PDE7B [13,14], and similar patterns of tissue expression have been described in humans and mice [15]. The PDE7A sub-type is predominantly expressed and functional in lymphocytes [16,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Details of this analysis are to be published. An important difference in the FMT gene list is that it included Pde7b, a high-affinity cAMP-specific phosphodiesterase anticipated to be upregulated in response to elevated PKA activity (Hetman et al, 2000), and Sphingosine kinase 1, which is functionally upregulated in response to PKA activation (Rius et al, 1997). …”
Section: Real Data Examplementioning
confidence: 99%